Giant Urinary Bladder and Bilateral Giant Hydronephrosis due to Bladder Neck Obstruction: One Case Report and Literature Review - Mohammed Fadl Tazi; Omar Riyach; Youness Ahallal; Soufiane Mellas; Abdelhak Khallouk; Mohammed Jamal El Fassi; Moulay Hassan Farih (Case Reports in Urology)
Bilateral hydronephrosis secondary to urinary obstruction leads to a buildup of back pressure in the urinary tract and may lead to impairment of renal function. Cases of giant hydronephrosis are rare and usually contain no more than 1-2 litres of fluid in the collecting system. Here, we report a rarely seen case with giant urinary bladder and bilateral giant hydronephrosis due to bladder neck obstruction which contains 4000 mL fluid in the collecting system of the kidney mimicking an ascites in an adult male.